"Fake news", dezinformacja, weryfikacja – szkoła wobec nadprodukcji informacji. - Wojtowicz, Katarzyna (Tomorrow’s school? Tradition and (r)evolutions in education, 2023)
The subject of this paper is one of the greatest threats to contemporary cultural reality – the creation and dissemination of fake news in the media space, as well as an attempt to answer whether and to what extent Polish language teaching responds to the need for students to acquire methods of content verification. The coronavirus pandemic, various social initiatives, and nowadays also the war in Ukraine clearly illustrate how powerful the content published on the Internet is and how vulnerable to it the recipients, unaware of manipulative procedures, may be. The aim of this article is to review school textbooks from the perspective of the presence of the above-mentioned problems in them, as well as to propose our own methodological solutions.